Integration of well log analysis data with geochemical data to evaluate possible source rock. Case study from GM-ALEF-1 well, Ras Ghara oil Field, Gulf of Suez-Egypt - A.A. El-Khadragy; T.F. Shazly; D.A. Mousa; M. Ramadan; M.Z. El-Sawy (Egyptian Journal of Petroleum)
Well logging methodology in geochemical evaluation is an important technique not only for its usefulness as a quick scan of potential source rock, but also in its ability to identify the organic richness (TOC%) of these rocks. Wireline logs can be used to identify source rock intervals in the primary stage of well drilling. Consequently, the logs used for source rock evaluations and calculation of Total Organic Carbon most commonly include density, sonic, gamma ray, neutron and resistivity by using several methods.In this research, a suite of geophysical logs and geochemical data were applied for determining the Total Organic Carbon content (TOC) and compare them together, in addition to source rock evaluation of the study formation.Application of such techniques take place in one well GM-ALEF-1 well located in the Ras Ghara oil Field, Gulf of Suez, Egypt, represented by Miocene rock, Rudeis Formation. A calculated TOC is compared with the measured one from the LECO SC632 after that Rock-Eval pyrolysis data also used to evaluate the TOC content mainly, organic richness, types of kerogen, and thermal maturity.The results of comparison showed that the Petrophysical method using ΔlogR and the LECO and Rock-Eval pyrolysis techniques have produced close results for Total Organic Carbon content, Hence it can be used as a fast and efficient way to regard the intervals rich in organic matter, further step takes place and the reach interval of organic matter is evaluated geochemically shows that the shale in Rudeis formation have fair to good organic richness, it has the potential to produce type II/III kerogen. It is marginally mature to mature source rock. The expected generated hydrocarbon is fair oil source with some gas. Keywords: Well logging, Total Organic Carbon (TOC), Source rock evaluation, LECO, Rock Eval pyrolysis and geophysical log data